1989
DOI: 10.1073/pnas.86.8.2868
|View full text |Cite
|
Sign up to set email alerts
|

Effects of recombinant insulin-like growth factor I on insulin secretion and renal function in normal human subjects.

Abstract: Insulin-like growth factor I (IGF-I) is an important mediator of growth hormone (GH) action and it appeared tempting to evaluate possible clinical applications. Recombinant IGF-I was infused s.c. at a dose of 20 jug/kg of body weight per hour during 6 days in two healthy adult subjects. Blood glucose and fasting insulin levels remained within normal limits and IGF-H levels were suppressed. In contrast to insulin, fasting C peptide levels were decreased. GH secretion was also suppressed by IGF-I. Our preliminar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
186
2

Year Published

1991
1991
2013
2013

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 298 publications
(206 citation statements)
references
References 20 publications
18
186
2
Order By: Relevance
“…Reduced IGF-1 levels may, in turn, partially account for the lower eGFR and increased risk for CKD that were observed in individuals with 1hPG Ն155 mg/dl. In fact, previous evidence indicated that plasma IGF-1 levels are associated with GFR (23), and infusion of recombinant IGF-1 increases GFR in normal individuals (24). There is evidence that IGF-1 enhances both renal blood flow and GFR by stimulating IGF-1 receptors (25).…”
Section: Discussionmentioning
confidence: 95%
“…Reduced IGF-1 levels may, in turn, partially account for the lower eGFR and increased risk for CKD that were observed in individuals with 1hPG Ն155 mg/dl. In fact, previous evidence indicated that plasma IGF-1 levels are associated with GFR (23), and infusion of recombinant IGF-1 increases GFR in normal individuals (24). There is evidence that IGF-1 enhances both renal blood flow and GFR by stimulating IGF-1 receptors (25).…”
Section: Discussionmentioning
confidence: 95%
“…In particular, a single injection of recombinant human IGF-I is able to lower blood glucose over a 3-hour period by increasing glucose uptake and inhibiting hepatic glucose production (2). At the same time, it is well-known that reduction of intra-abdominal fat improves insulin sensitivity in peripheral tissues.…”
Section: Post-vlcd Correlationsmentioning
confidence: 99%
“…Data concerning IGF-I concentrations in patients with obesity are not unanimous, because they have been reported to be lower, equal, or even higher than in lean, age-matched controls (2,3,5,21).…”
Section: Introductionmentioning
confidence: 99%
“…The anti-insulin monoclonal antibody was from Sigma. The anti-IGF-1 receptor and anti-insulin receptor antibodies were from Santa Cruz Biotechnology; both antibodies were raised against the N-terminal unique sequences (amino acids [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] of the corresponding receptor. IGF-1 was from Becton Dickinson or GIBCO͞BRL.…”
Section: Methodsmentioning
confidence: 99%
“…Insulin-like growth factor 1 (IGF-1) is one such example. When infused into normal healthy human subjects at a dose not causing hypoglycemia, IGF-1 can decrease the circulating insulin level (2) and IGF-1 can directly attenuate insulin secretion from isolated primary rat pancreatic ␤ cells (3). Insulin itself has been postulated to exert a negative-feedback control of its own secretion (4,5).…”
mentioning
confidence: 99%